Colorectal cancer and associated genetic, lifestyle, cigarette, nargileh-hookah use and alcohol consumption risk factors: a comprehensive case-control study - Bener, Abdulbari; Öztürk, Ahmet Emin; Dasdelen, Muhammed Furkan; Barisik, Cem Cahit; Dasdelen, Zehra Betul; Agan, Ahmet F.; De La Rosette, Jean; Day, Andrew S. (Oncology Reviews, 2024)
Aim: This study aimed to investigate the causes and risk factors of colorectal cancer (CRC) in a Turkish population, focusing on various modifiable and non-modifiable risk factors.A hospital-based case-control design was employed to compare individuals with CRC (cases) to individuals without CRC (controls). Male and female participants were recruited from the surgery, internal medicine, and out-patient departments. The study encompassed socio-demographic data, clinical information, radiological diagnoses, and biochemical measurements. Univariable and multivariable logistic regressions were used to determine associated risk factors of CRC.The study included 704 individuals with CRC and 704 controls. Significant socio-demographic disparities were observed between the groups, with over 30% of the cases having lower levels of education and income compared to the controls. Lifestyle factors such as obesity, higher rates of smoking (cigarettes and hookah) and alcohol consumption were more prevalent among cases than controls. Further significant associations were identified with intestinal inflammation, obesity, processed food consumption, and symptoms such as abdominal pain, cramps, diarrhea, constipation, blood in stool, bloating, irritable bowel syndrome, nausea/vomiting, anemia, stress, fatigue, weakness, and weight loss. Diet analysis revealed that individuals with CRC consumed more red meat, processed and fast foods along with less pulses and vegetables. Genetic predispositions and exposure to chemicals also correlated strongly with increased CRC risk. Multivariable regression analysis identified, nausea/vomiting, constipation, intestinal disease, genetics factor, hookah-nargileh use, history of any cancer, family history of bowel cancer, constipation, cigarette smoking, stress, milk-yogurt consumption, obesity and red meat consumption as significant determinants for CRC.CRC risk is influenced by dietary, lifestyle, and genetic factors. Awareness of hereditary risk and participation in screening are crucial. Lifestyle changes, such as avoiding smoking, hookah, and alcohol use, and adopting a healthy diet, are essential for prevention.1.